2021
DOI: 10.3390/cancers13020315
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Hyperplasia with Lymphoepithelial Sialadenitis (LESA)-Like Features: Strong Association with Lymphomas and Non-Myasthenic Autoimmune Diseases

Abstract: Thymic hyperplasia (TH) with lymphoepithelial sialadenitis (LESA)-like features (LESA-like TH) has been described as a tumor-like, benign proliferation of thymic epithelial cells and lymphoid follicles. We aimed to determine the frequency of lymphoma and autoimmunity in LESA-like TH and performed retrospective analysis of cases with LESA-like TH and/or thymic MALT-lymphoma. Among 36 patients (21 males) with LESA-like TH (age 52 years, 32–80; lesion diameter 7.0 cm, 1–14.5; median, range), five (14%) showed ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The German cohort included 15 (19,5%) type A thymomas, 31 (40,3%) type AB, 15 atypical A/AB (19,5%) and 16 (20,8%) type B1-B3 thymomas. The remaining 24 German cases comprised 18 thymic carcinomas, 2 cases of sclerosing mediastinitis, 2 metaplastic thymomas, 1 thymolipoma and 1 thymic hyperplasia with lymphoepithelial sialadenitis (LESA)-like features ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The German cohort included 15 (19,5%) type A thymomas, 31 (40,3%) type AB, 15 atypical A/AB (19,5%) and 16 (20,8%) type B1-B3 thymomas. The remaining 24 German cases comprised 18 thymic carcinomas, 2 cases of sclerosing mediastinitis, 2 metaplastic thymomas, 1 thymolipoma and 1 thymic hyperplasia with lymphoepithelial sialadenitis (LESA)-like features ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thymic hyperplasia with lymphoepithelial sialadenitis-like features was assumed to be unrelated to autoimmune diseases; however, Porubsky et al reported a series of 36 cases in which they described that thymic hyperplasia with lymphoepithelial sialadenitis-like features was strongly associated with lymphomas and non-myasthenic autoimmune diseases. 5 In their case series, 5 cases had an accompanying B-cell lymphoma (4 MALT lymphomas and 1 diffuse large B-cell lymphoma). In comparison, 12 cases had an accompanying autoimmune disorder (4 systemic lupus erythematosus, 3 rheumatoid arthritis, 2 myasthenia gravis, 2 asthma, Sjogren's syndrome, scleroderma, pure red cell aphasia, Grave's disease, and anti-IgLON5 syndrome).…”
Section: Discussionmentioning
confidence: 97%
“…The lesion is characterized by expansion of epithelial cell meshworks with prominent lymphoepithelial lesions, numerous Hassall corpuscles undergoing cystic changes, a substantial or even complete cortical atrophy, and lymphofollicular hyperplasia, potentially resulting in an organ appearance reminiscent of a lymph node (Figure 2). The largest cohort published so far showed a slight male predominance and a mean age of 52 years (range 32–80 years) 17 . Moreover, it revealed that 14% of the patients had an associated lymphoma, in most cases a thymic MALT lymphoma, and 33% of the patients suffered from nonmyasthenic autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis, scleroderma, Sjögren syndrome, pure red cell aplasia, or Graves' disease (Figures 3 and 4).…”
Section: Anterior Mediastinal Tumoursmentioning
confidence: 94%
“…The largest cohort published so far showed a slight male predominance and a mean age of 52 years (range 32-80 years). 17 Moreover, it revealed that 14% of the patients had an associated lymphoma, in most cases a thymic MALT lymphoma, and 33% of the patients suffered from nonmyasthenic autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis, scleroderma, Sj€ ogren syndrome, pure red cell aplasia, or Graves' disease (Figures 3 and 4). These findings indicate that LESA-like TH is not merely an aggravated form of a TFH, but rather an entity of its own standing and that a haematologic and rheumatologic work-up should be warranted in patients diagnosed with LESA-like TH.…”
Section: R E B O U N D H Y P E R P L a S I A O F T H E T H Y M U Smentioning
confidence: 98%
See 1 more Smart Citation